Ecological Crisis, Development and Capital Contradictions in Latin America - Galafassi, Guido Pascual (2013)
This article is about the social and ecological crisis in Latin America which is closely related to the social and economic development process. The underdeveloped economy has determined the general features of the rural and urban regions. Poverty, social exclusion and environmental conflicts are some of the general consequences of the capital contradictions which define an underdeveloped process of growth. To analyse the social and environmental conditions of Latin-American urban and rural regions it is necessary to take into account three main factors: the contradiction between capital and production conditions (nature, space and labourpower), the underdeveloped economy which has determined high levels of inequality and social exploitation, and the exploitation process of natural resources based on a pillage economy. The imported market economy in Latin America, as a bad copy of the growth economy in the North, has generated a highly unequal development. The acceleration of the economic growth has gone hand in hand with the deceleration of the development. Whereas the macro-economic rates improve, the indicators that measure qualitative evolution among sectors, territories and people have deteriorated. So, to explain the ecological crisis in Latin America, it is important to consider not only the different forms of environmental impacts, but also the socio-economic factors and the contradictions in capitalistic development. Therefore, this article is aimed to describe the general social and economic development process in Latin America, and also to examine the relationship among industrialization, natural resources exploitation and urbanization related to the social and ecological conditions in urban and rural areas. In order to analyze the above mentioned relation between development and ecological crisis it is important to pay attention to new theories that can give us a better idea on the relationship between society and nature. The traditional interpretations on Latin American development have not taken into account the complexity of existing relations among socio-economic, political and environmental aspects since these interpretations mainly conceive society "disconnected" from its natural surroundings. Therefore, these lines of thought are not capable of considering the interrelations, influences and conditioning that define the historical processes, which are always (directly or indirectly) constructed from an articulation of social and natural processes. Thus, to study the relationship among society, nature and development it is necessary to consider one of the basic tendencies of capital: to debilitate and to destroy its own production conditions. Production conditions refer to external physical conditions or environment, communal conditions like regional or urban infrastructure and personal conditions of labourpower. The basic tendency of capital mentioned above is precisely explained by the theory of second contradiction of Capitalism (O´Connor, 1988). The first contradiction of Capitalism (between forces and relations of production - capital against work-) is internal to the system; it has nothing to do with the conditions of production. The second contradiction of Capitalism “focuses on the way that the combined power of capitalist production relations and productive forces self- destruct by impairing or destroying rather than reproducing their own conditions ("conditions" defined in terms of both their social and material dimensions)” –i.e. capital against nature, labourpower and space-. An intense and continuous exploitation of natural resources as well as spatial and labourpower general conditions is needed for Capital to valorise itself. “The basic cause of the second contradiction is capitalism's economically self-destructive appropriation and use of laborpower, urban infrastructure and space, and external nature or environment -- `selfdestructive´ because costs of health and education, urban transport, home and commercial rents, and the costs of extracting the elements of capital from nature will rise when private costs are turned into <social costs>". In the first contradiction the rate of work exploitation as a clearly remarkable element that assumes an excluding theoretical importance is identified, while in the second contradiction a unique term that summarizes the totality does not exist. That is why it is possible today to find a multiplicity of social movements with diverse vindications. So, new social movements –together with the historical labourpower movement- are the agencies of current social transformation, which represent new social struggles including, among others, struggles within production over workplace health and safety, toxic waste production and disposal, natural resources exploitation, urban conditions of life, radical democracy patterns to solve problems and to take social and political decisions.